The Impact of Exclusion in School: A Comprehensive Study in New York City, 2010-2015 - Hassoun Ayoub, Lama ([Verlag nicht ermittelbar], 2020)
This study uses quantitative and qualitative research to fill a gap in the scholarly literature on "what works" in school discipline, climate, and safety and has important implications for educators and justice policymakers nationwide. The quantitative analysis utilized data from 2010-2015 of middle and high school students (N=87,471 students nested within 804 schools and 74 neighborhoods) in New York City. Researchers applied hierarchical modeling methods to analyze effects of neighborhood, school, and student characteristics on: 1) future school disciplinary outcomes; 2) future arrest; and 3) grade advancement. Demographic variables for individual participants include race, gender, and if they are an English language learner. Demographic variables for neighborhoods include race, median income, crime rates, and education levels.